ANALISIS PENGARUH RETURN ON INVESTMENT (ROI), RETURN ON EQUITY (ROE), RATE OF RETURN (ROR), DAN PROFIT MARGIN TERHADAP CASH DEVIDEN PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - B51109010, Asri Hidayati (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
The development of pharmacy companies have given significant effect to the economic growth in Indonesia. Together with this opportunity, it will clearly influence the investors to take decision in investing. In investing, what is most expected by the investors is the Capital Gain and Devidend. The number of Capital Gain and Devidend will be influenced by the number of investment which is made by the investors toward the invested company. Cash dividend is a kind of the most common dividend payment which is paid to the shareholders. This cash dividend is influenced by some factors; external and internal factors. The purpose of this research is to find out the influence of Return on Investment (ROI), Return on Equity (ROE), Rate of Return (ROR), and Profit Margin toward Cash Dividend on the pharmacy company which is registered in Indonesia Stock Exchange. In this research, the analyzed company is the registered pharmacy company in Indonesia Stock Exchange which 5 years lately has done the division of cash dividend, since 2007 until 2011. Based on the result of research by using the SPSS for Windows 19.0 computer program, shows that if the use of independent variable is in form of Return on Investment, Return on Equity, Rate of Return and Profit Margin, so in this classical assumption test there is one unfulfilled test; the multicollinearity test. There is a multicollinearity symptom between the Return on Investment variable and Return on Equity. In order to get the unbiased result, so the new multiple regression models have been made by getting out the Return on Equity variable because it has a smaller t- count than the t- count of Return on Investment. It shows that the Return on Investment variable has stronger influence on Cash Dividend than the Return on Equity variable. All in all, based on the new multiple regression models, it has been concluded that Return on Investment, Rate of Return and Profit Margin partially or simultaneously have a significant influence toward Cash Dividend on the pharmacy company which is registered in Indonesia Stock Exchange. Return on Investment, Rate of Return, and Profit Margin have 45.1 percent influence on Cash Dividend, while 54.9 percent is influenced by other factors. Keywords : Return on Investment, Return on Equity, Rate of Return, Profit Margin, Cash Deviden